Economic analysis of sheep rearing in Mathura district of Uttar Pradesh - DEOGHARE, P R; BHATTACHARYYA, N K (The Indian Journal of Animal Sciences, 2013)
TheÂ capital investment/sheep a year was highest on small farms (Rs 772.09), followed by marginal farms (Rs 763.17) and landless sheep keepers (Rs 733.36). The margin of profil on small farms was much higher than of landless sheep keepers and marginal farms. The overall return overcost A (paid out expenses and depreciation) was Rs 4 146.62, over cost B (cost A+intereston fixed capital) was Rs 3 203.20 and over cost C (cost B + input value of family labour) was Rs 902.05.